Water sanitation and hygiene in the schools of rural field practice area of Shri B. M. Patil Medical College, Vijayapur - Hullalli, Rashmi; Gudadinni, M. R.; Patil, Shailaja S. (International Journal Of Community Medicine And Public Health, 2017)
Background: One of the world’s most urgent issues is lack of safe water, sanitation and hygiene. Water-related improvements are crucial to meet the development goals, reduce child mortality, and improve health in a sustainable way. The absence of WASH in schools is responsible for 20% of total deaths and disability adjusted life years (DALYs) in children. Over 440 million schools days are missed annually due to water, sanitation and hygiene related diseases. Though there are emerging vaccines for rotavirus and cholera still WASH remains critical in the prevention of diarrheal diseases, soil transmitted helminthes infections and acute respiratory diseases. Objective of the study was to study the implementation and functionality of WASH in schools. Methods: A cross sectional study was done in all the schools of rural practice area of our college by interview technique using a pre tested semi structured questionnaire. Results: Out of 7 schools, 5 (71%) had piped water supply but only 2 schools (28.5%) practiced the process of water purification every day. All the schools were provided with toilet facilities whereas only 3 schools had separate toilet for girls. When looked upon availability of soap only 3 schools had provided soap regularly for hand washing. Most of the schools taught about personal hygiene but only 2 schools revealed that they dispose solid waste regularly. Conclusions: Although nationwide emphasis is given to water sanitation and hygiene, practicing is very low especially in rural areas. Therefore special efforts should be done not only for the implantation, but also upon the operation and maintenance of the same.